A fast on-site measure-analyze-suppress response to control vortex-induced-vibration of a long-span bridge. (January 2022) - Zhao, Lin; Cui, Wei; Shen, Xiaomin; Xu, Shengyi; Ding, Yejun; Ge, Yaojun
Highlights: Water-filled barrier was the direct causes of initial large VIV on Humen Bridge. Subsequent VIV continued at smaller amplitude due to the decreased damping. Spoiler installed on handrail was effective in reducing the VIV amplitude. Abstract: Vortex-induced vibration (VIV) occurred on Humen Bridge starting from May 5th, 2020. The direct reason was that the water-filled barriers were placed along the two edges of the bridge deck upper surface, which destroyed the streamlined aerodynamic shape configuration and, therefore, vortices were generated along the bridge section. With the help of several portable monitoring devices, wind speeds, structural motion, and airflow at the wake of the bridge section can also be recorded separately. After removing the barriers, subsequent VIV was continuing due to the decreased structural damping. The amplitude was smaller than the initial case, but still exceeded the threshold defined in Chinese bridge specification. The spoiler was proposed to be installed on the handrail to mitigate vortex and suppress VIV. The Doppler LiDAR detected that the vortex frequencies had been distorted after installing the spoiler, and bridge motion also had dramatically reduced to below the threshold when the wind climate kept as a similar condition when previous VIV happened. Therefore, the bridge administrative agency and local government decided to reopen Humen Bridge after ten days of closure.